A história da África e dos afrodescendentes vai à escola: a Lei 10.639/2003 e os saberes docentes - Correa Junior, Rui Leon Aenlhe [UNIFESP] (2019)
From the interview of three teachers and two teachers of History of the Municipal Education Network of the City of São Paulo, this work seeks to understand how the teaching of African History and the African descendants has been taught, since, since 2003, we have a Law (10.639 / 2003) that mandates the teaching of the subject in question. In this sense, it supports us theoretically in the elaborations of Maurice Tardif, with regard to the concept of teaching saber, and in the elaborations of Ivor Goodson (1995 and 1992), a respect for the importance of the teacher's life trajectory. Still, the discussions about respect for the teacher's professional life cycle presented by Huberman (2000). Teachers who already work or work with a thematic proposal in the Law are privileged, as well as this work is imbued with considering a life trajectory of teachers and the moment of their careers. Given the importance of investigating how the teacher teaches his classes, we seek teachers and teachers at different points in their career. You can also understand or understand who led history teachers, without understanding their motivations, inspirations, and even frustrations, to analyze how they can articulate life history, knowledge, and experiential knowledge. Therefore, we also sought to interview teachers who graduated before or after the Law, adding teachers who graduated from public and private universities, with no sense of thinking how their initial education influenced or influenced work. Finally, the values ​​of the methodologies of oral history allow to look beyond the first layer of the relationship of teachers.